German construction industry: Refurbishment lacks momentum, new residential construction gets second wind - Martin Gornig; Christian Kaiser; Claus Michelsen (DIW Economic Bulletin, 2015)
The construction industry has been a key pillar of the German economy in recent years. New residential construction played a major part in this with the volume of new construction growing nominally by over 60 percent between 2010 and 2014. The development of construction work on existing residential buildings was less dynamic, however, with just under ten-percent growth between 2010 and 2014. A key reason for this is the declining volume of investment in energy-efficiency of residential buildings. Similar growth is anticipated for the German construction industry as a whole in 2015. Construction activity will continue to boost the economy into 2016. In addition to residential construction, commercial construction and sharp increases in the volume of public construction, largely triggered by the major refugee influx, are expected to provide a positive impetus. Gradually, the German government's plans to increase investment in transportation routes and municipal infrastructure should also start to have a palpable impact.
Keywords: E32; E66; 330; construction industry; green retrofits; energy efficiency investment; economic outlook